Julie Coleman and Anne McDermott (Editors). Historical Dictionaries and Historical Dictionary Research: Papers from the International Conference on Historical Lexicography and Lexicology at the University of Leicester, 2002. - Du Plessis, J.C.M.D. (Lexikos, 2006)
The papers collected in this volume were originally presented at an International Conference on Historical Lexicography and Lexicology organized by Julie Coleman, and meant to fill the gap created by the two International Round Table Conferences in Florence and Leyden in 1971 and 1977 respectively. The purpose of the conference was to bring together scholars and academics working in the field of historical lexicography, whether researching the history of historical dictionaries or whether compiling dictionaries with a historical point of departure. Accordingly the collection, competently edited and introduced by Julie Coleman and Anne McDermott, is arranged in two sections, reflecting the distinction between those researchers tracing the historical development of dictionaries and those practitioners faced with the problems and challenges of the compilation of historical dictionaries. The first part dealing with the history of dictionaries consists of twelve papers (two-thirds of the book), while the second part dealing with the practice of historical dictionaries consists of six papers (one-third of the book).